Iodine Promoted Ultralow Zn Nucleation Overpotential and Zn-Rich Cathode for Low-Cost, Fast-Production and High-Energy Density Anode-Free Zn-Iodine Batteries - Zhang, Yixiang; Wang, Lequan; Li, Qingyun; Hu, Bo; Kang, Junming; Meng, Yuhuan; Zhao, Zedong; Lu, Hongbin (Nano-Micro Letters, 2022)
The anode-free design is a promising strategy to increase the energy density of aqueous Zn metal batteries (AZMBs). However, the scarcity of Zn-rich cathodes and the rapid loss of limited Zn greatly hinder their commercial applications. To address these issues, a novel anode-free Zn-iodine battery (AFZIB) was designed via a simple, low-cost and scalable approach. Iodine plays bifunctional roles in improving the AFZIB overall performance: enabling high-performance Zn-rich cathode and modulating Zn deposition behavior. On the cathode side, the ZnI2 serves as Zn-rich cathode material. The graphene/polyvinyl pyrrolidone heterostructure was employed as an efficient host for ZnI2 to enhance electron conductivity and suppress the shuttle effect of iodine species. On the anode side, trace I3− additive in the electrolyte creates surface reconstruction on the commercial Cu foil. The in situ formed zincophilic Cu nanocluster allows ultralow-overpotential and uniform Zn deposition and superior reversibility (average coulombic efficiency > 99.91% over 7,000 cycles). Based on such a configuration, AFZIB exhibits significantly increased energy density (162 Wh kg−1) and durable cycle stability (63.8% capacity retention after 200 cycles) under practical application conditions. Considering the low cost and simple preparation methods of the electrode materials, this work paves the way for the practical application of AZMBs. Highlights: 1 The I3− additive promoted in situ formation of zincophilic Cu nanoclusters on commercial Cu foil, which achieves uniform Zn deposition with ultralow nucleation overpotential and high reversibility. 2 The Zn-rich ZnI2 cathode confined by graphene/polyvinyl pyrrolidone heterostructure shows enhanced conductivity and shuttle effect suppression, providing sufficient Zn2+ for the anode stably. 3 The assembled anode-free Zn-iodine battery exhibits attractive features for commercialization: low cost, fast production, significantly increased energy density and durable cycle stability under practical application conditions.